Identifying sources of preservice teachers’ dyslexia knowledge to guide teacher education - Chambre, Susan J.; Anderson, Alida (Frontiers in Education, 2025)
This paper presents findings from an exploratory descriptive qualitative inquiry of preservice teachers’ (PSTs’) self-reported dyslexia knowledge sources. The purpose of this research is to provide a baseline understanding of how and where PSTs’ understandings of dyslexia originate to inform teacher educators about sources of misconceptions and to support PSTs’ conceptual growth about dyslexia. Seventy-six PSTs in the United States completed written responses to online learning module questions about dyslexia knowledge sources. Sources of PSTs’ dyslexia knowledge were identified via thematic coding, to include popular media, friends or acquaintances, college coursework, and family. Findings indicate PSTs’ dyslexia knowledge as stemming from sources that perpetuate misconceptions of dyslexia. Discussion centers on the implications of identifying PSTs’ initial knowledge sources for teacher preparation research and practice by guiding PSTs’ conceptual growth regarding dyslexia.